Seismic assessment of existing reinforced concrete buildings - Oliveira, João Mário Dias de (2014)
This dissertation aims to the discussion and application of tools and processes which allows to assess the non-linear behaviour of a reinforced concrete structure. When a numerous amount of buildings was built in concrete, in a period when the regulations did not have the design philosophy for the occurrence of earthquakes, it is important to carry out full and e ective structural assessments. Among several possibilities to make the evaluation as, simpli ed, linear analysis and static non-linear analysis, the non-linear dynamic can provide the most approximate numerical behaviour compared to the real one. With the potentialities of the computers, it is possible to run the analysis with this complex simulation using dynamic excitations of real earthquakes. It is made a historical reference of numerical models which simulates the behaviour of materials, and the ones integrated on the analysis are further explored. Is presented the study cases, its assumptions and some procedures that should be applied in structural modelling. The discussion is divided in two groups. On the rst the global analysis is discussed in terms of global behaviour, deformations and progression of forces, and on the second group is referred to the local assessment of structural elements. The local analysis has some comparisons between di erent interpretations of the code and also regarding the Italian code. Is analysed the bond-slip mechanism due to the smooth bars in some elements, which better simulates the global response of the structures.